Correções vibracionais para as segundas hiperpolarizabilidades de clusters AlnPn - Feitoza, Luan da Silva (2015)
This work presents the vibrational contributions for the static and dynamic second hyperpolarizabilities of the clusters Al2P2, Al3P3, Al4P4, Al6P6 and Al9P9. The optimized geometries and the calculations of harmonic vibrational frequencies, dipole moments ( ), polarizabilities ( ) and first hyperpolarizabilities ( ) were performed at the MP2 level along with the basis set aug-cc-pVDZ using the GAUSSIAN 09 program. The calculations of vibrational corrections were performed using the perturbation theoretical method of Bishop and Kirtman (PT) and a variational methodology (VAR) developed in our research group. The outcomes show that the vibrational corrections have the same magnitude order of electronic contributions, therefore cannot be neglected. The results also showed that PT method is sufficient to obtain the most relevant terms, [ 2] and [ ], but there are limitations to compute the term [ 2 ], which is related to the system anharmonicities. The vibrational corrections by atom have a similar convergence trend to that exhibited by the related electronic contribution by atom as the number of atoms increases. The nonlinear optical processes IDRI, dc-SHG and dc-K were studied for the dynamic vibrational corrections. Dynamic results reflect static vibrational results. In particular, the frequencies of the modes that contribute most in the static limit are associated with the peaks of the second dynamic hyperpolarizability.